Efficacy of the prophylactic use of octreotide for the prevention of complications after pancreatic resection: An updated systematic review and meta-analysis of randomized controlled trials. Issue 29 (July 2017) - Wang, Chunli; Zhao, Xin; You, Shengyi
Abstract: Background: The use of octreotide prophylaxis in the prevention of complications after pancreatic resection remains controversial. The aim of this systematic review and meta-analysis was to evaluate the efficacy of octreotide prophylactic treatment to prevent complications after pancreatic resection. Methods: Five databases (PubMed, Medline, SinoMed, Embase, and Cochrane Library) were searched for eligible studies from 1980 to November 2016 with the limitation of human subjects and randomized controlled trials (RCTs). Data were extracted independently and were analyzed using RevMan statistical software version 5.3 (Cochrane Collaboration, http://tech.cochrane.org/revman/download ). Weighted mean differences (WMDs), risk ratios (RRs), and 95% confidence intervals (CIs) were calculated. Cochrane Collaboration risk of bias tool was used to assess the risk of bias. Results: Twelve RCTs comprising 1902 patients were identified as eligible. The methodological quality of the trials ranged from low to moderate. A pooled analysis of effectiveness based on the data from each study revealed that octreotide could significantly reduce the rate of pancreatic fistula (PF) after pancreatic resection (RR = 0.75, 95% CI = 0.57–0.98, P  = .04). The same findings were discovered in multicenter and European subgroups with a subgroup analysis; no obvious differences were noted in American, Asian, and single-center subgroup analyses. An equal effect was observed between the use or non-use of octreotide groups regarding mortality (RR = 1.24, 95% CI = 0.77–2.02, P  = .38). Octreotide had no advantages in regards to mortality improvement. The total numbers of complications associated with the use or non-use of octreotide were similar (RR = 0.77, 95% CI = 0.58–1.03, P  = .08). Among the high-risk group, octreotide was more effective in reducing complications (RR = 0.61, 95% CI = 0.46–0.82, P  = .0009). Compared with the patients who did not receive prophylactic treatment, the patients who underwent pancreatic resection benefited from octreotide because it had better efficacy in preventing fluid collection and postoperative pancreatitis. Conclusion: The prophylactic use of octreotide is suitable for preventing postoperative complications, especially PF and fluid collection as well as postoperative pancreatitis. However, no obvious differences were noted regarding mortality. In view of the clinical heterogeneity and varying definitions of PF, whether these conclusions are broadly applicable should be further determined in future studies. Abstract : Supplemental Digital Content is available in the text